2010
DOI: 10.1063/1.3361199
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the electron energy distribution and E-H mode transition in inductively coupled nitrogen plasma

Abstract: Electron energy distribution function ͑EEDF͒ measurements were conducted in nitrogen gas inductively coupled plasma ͑ICP͒. At a low ICP power ͑capacitive mode͒ and a high gas pressure, the measured EEDF had an unusual distribution with a hole near this electron energy of 3 eV. This distribution is primarily due to vibrational excitation collisions because the vibrational cross section has a sharp peak at the electron energy in nitrogen gas. However, the EEDF evolved into a Maxwellian distribution and the hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Turner et al 7 showed evidence of vibration excitation collisions through the EED measurement in N 2 gas CCP. A similar result for vibration excitation collisions was confirmed by Lee et al 21 in the capacitive mode (E mode) of the ICP. Ren et al 22 showed that the actual loss of kinetic energy for electrons and ions that strongly depend on the EED.…”
Section: Introductionsupporting
confidence: 83%
“…Turner et al 7 showed evidence of vibration excitation collisions through the EED measurement in N 2 gas CCP. A similar result for vibration excitation collisions was confirmed by Lee et al 21 in the capacitive mode (E mode) of the ICP. Ren et al 22 showed that the actual loss of kinetic energy for electrons and ions that strongly depend on the EED.…”
Section: Introductionsupporting
confidence: 83%
“…1, 16 One possible explanation for this trend in T e may be the dramatic evolution of the EEPF through the electron heating effect 11,21,[30][31][32][33][34][35][36][37] or electronelectron collisions. 17,26,38,39 However, our experiment was conducted in plasmas having nearly Maxwellian EEPFs. As shown in Fig.…”
mentioning
confidence: 99%
“…It is remarkable because, in oxygen containing plasmas, the degradation processes at higher temperatures are accompanied of oxygen functionalization of the organic sample, leading to production of resistant products [25]. H-mode is known to have a higher ion temperature than E-mode [12,13,15] and this is a considerable source of heating in plasmas. Additionally, the higher electron density and electron energy distribution function (EEDF) at lower values, found in H-mode, can also lead to dissociative electron attachment (DEA) on sample surface, which could also increase heating by bond dissociation [26].…”
Section: Resultsmentioning
confidence: 99%
“…, while H-mode ranges from 10 10 to 10 11 cm -3 at the same applied power [8,10,11]; the plasma potential is reduced at the H-mode even with the increase of applied power [12,13]; the EEDF changes to a more Maxwellian electron distribution at the Hmode [9,10,14]; electron temperature is reduced at H-mode, while gas temperature is increased [13][14][15]; electron-electron collision frequency is greatly increased [12]; after the H-mode is initiated, it can be sustained even at lower powers [12,16]; finally, both E and H modes can coexist inside the reactor [9].…”
Section: Introductionmentioning
confidence: 99%